Retronasal odor perception requires taste cortex but orthonasal does not - Blankenship, Meredith L. (Curr Biol, 2018)
Smells can arise from a source external to the body, and stimulate the olfactory epithelium upon inhalation through the nares (orthonasal olfaction). Alternatively, smells may arise from inside the mouth during consumption, stimulating the epithelium upon exhalation (retronasal olfaction). Both ortho- and retronasal olfaction produce highly salient percepts, but the two percepts have very different behavioral implications. Here, we use optogenetic manipulation in the context of a flavor preference learning paradigm to investigate differences in the neural circuits that process information in these two sub-modalities of olfaction. Our findings support a view in which retronasal, but not orthonasal odors share processing circuitry commonly associated with taste. First, our behavioral results reveal that retronasal odors induce rapid preference learning, and have a potentiating effect on orthonasal preference learning. Second, we demonstrate that inactivation of the insular gustatory cortex selectively impairs expression of retronasal preferences. Thus, orally-sourced (retronasal) olfactory input is processed by a brain region responsible for taste processing, whereas externally-sourced (orthonasal) olfactory input is not.